Khalfīyat wa taḥaddīyāt al-aqalīyah al-muslimah al-Ṣīnīyah fi Pontianak - Hermansyah, Hermansyah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Chinese Indonesians are not homogeneous community. Study of the Chinese is also important to understand not only their presence in Indonesia but also religious life. This article seeks to shed light on Indonesia’s Chinese Muslims in Pontianak City. It explains the reasons that led the Chinese Indonesians to convert to Islam and the challenges they face. Several important reasons behind their conversion, among others, are intellectuality, morality, social relations, and mysticism. In contrast with conversion to other religions, a Chinese Indonesians conversion to Islam is such problematic. This is mainly due to the negative stereotype against Muslims. It has also been worsened by the behavior of religious fanaticism of some Muslims under the banner of fundamentalism. Thus, those who are converting to Islam, to some extent, have experienced various challenges such as rejection from family members as well as their original community, and some of them also receive death threats. Besides, they even had to forsake their Chinese identity.DOI: 10.15408/sdi.v25i1.6034